A cost-effective optimized design of a 3D NAND staircase integration flow - Zhang, Jinzhi (Nanyang Technological University, 2023)
A Cost-Effective Optimized Design of a 3D NAND Staircase Integration Flow is based on comparing new-generation technology for 3D NAND manufacturing with old-generation technology and proposes an optimized design for a process integration-based 3D NAND stepped module manufacturing process. In the new generation of 3D NAND manufacturing technology, the cleaning step reaction environment has been upgraded, and the more critical etch-stop layer in this structure is no longer exhumated as it was in the old-generation technology. This design is based on this and proposes a design for optimizing the etch-stop layer protection step. The design is conceived as a controlled variable experiment, where the control group will continue to maintain all the settings of the original 3D NAND manufacturing process, while the experimental group will use the optimized process proposed in this design. This experiment also demonstrates the feasibility of the design by examining several aspects of the experimental data that do not introduce any failure modes to the subsequent process or affect the performance of the subsequent data. Finally, this design was calculated to reduce the total manufacturing time for 3D NAND by 2% and generate a cost reduction of S$10,140,000 by streamlining the process of manufacturing the modules without affecting any subsequent manufacturing process of 3D NAND and its performance.